Book review: Yoginder Kumar Alagh, Economic Policy in a Liberalising Economy: Indian Reforms in This Century. Issue 1 (April 2021) - Kumar, Surinder
Yoginder Kumar Alagh, Economic Policy in a Liberalising Economy: Indian Reforms in This Century . Singapore: Springer, 2018, 89+xiii pp., ₹5, 060, ISBN: 9789811328169 (Paperback).